Engineering strain to achieve stable 92Zr targets on carbon backing. (November 2017) - Khushboo,; Abhilash, S.R.; Umapathy, G.R.; Duggal, H.; Kabiraj, D.; Mandal, S.
Abstract: Importance of substrate heating for fabrication of strong zirconium targets ( 92 Zr) has been discussed. The targets have been prepared using experimental facilities of target laboratory at Inter University Accelerator Centre (IUAC), New Delhi, India. Substrate heating has been tried for the first time for the fabrication of carbon backed zirconium targets. The heating of substrate exhibited improved stability, longevity and a better success rate of production of targets. In addition, a large number of wrinkle-free targets have been obtained using this technique. Elemental analysis has been performed to determine purity of the targets with X-ray fluorescence and Rutherford back-scattering spectrometry methods. These targets have successfully survived against high flux heavy ion bombardment viz. 14 N and 28 Si. Highlights: The targets of 92 Zr are fabricated on carbon backing using electron beam evaporation method. Substrate heating has been tried for the first time for fabrication of the targets. Substrate temperature has been optimized prior to final deposition of 92 Zr. The characterization of targets by different techniques confirmed the purity of the targets. These targets have successfully survived against high flux heavy-ion beam.